School management and decision-making in Ethiopian government schools - Abebe, W (Young Lives, 2012)
Both academic and policy documents indicate that poor school management and decision-making at local level are major challenges in creating equitable access to good-quality education in Ethiopia. In principle, educational provision can be improved through better management practices, transparency in the use of resources and accountability to all stakeholders (community, parents, students, teachers, etc.). This study focuses on school management and decision-making in government schools and is based on the qualitative data collected in 2010 as part of the Young Lives school survey. The paper examines the extent to which the involvement of different stakeholders in schools (teachers, headteachers, parents, students, local government administration, etc.) impacts upon critical decision-making at school level. The paper uses qualitative data collected as part of the recent Young Lives school-based research from five of the 20 sentinel sites. Specifically it uses data collected through in-depth interviews with teachers and headteachers. It is only in recent years that the Ethiopian Government has paid attention to the importance of school management and school-level decision-making. Research in the area of school management is almost nonexistent in Ethiopia. However, various reports and policy documents prepared by the Federal Ministry of Education clearly indicate the extent to which the Government has been focusing on improving school management in recent years (MOE 2005; MOE 2010a). The paper examines how headteachers and teachers contribute to the strengthening of the day-to-day management and supervision of schools attended by Young Lives case study children.